Mad river - Beatty, Jan, 1952- (Pitt poetry series., 1995)
""In every poem, she keeps her fury contained, but omnipresent, so that it resembles a cornered dog's warning growl, yet she hints of happier possibilities.""--Booklist""Beatty does offer deeply visceral and sensory work, especially in the second and third sections of this three-part book. ... She risks relative boldness and deep emotional commitment, disregarding political correctness in respect for this less readily sanitized realm of experience.""--Publishers Weekly""Her poems speak to us head-on, with courage and a contemporaneous eloquence."" --Yusef Komunyakaa""Raw, energetic, gritty